2020
DOI: 10.1186/s12882-020-01791-z
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic peritonitis and nephrotic syndrome in Kimura’s disease: a case report and literature review

Abstract: Background: Eosinophilic peritonitis is a relatively rare entity. Kimura's disease is a rare chronic inflammatory disorder of unknown etiology, characterized by subcutaneous nodules mainly in the head and neck region, regional lymphadenopathy and occasional involvement of kidney. There is currently no report of eosinophilic peritonitis in Kimura's disease. Case presentation: A 44-year-old Chinese man presented with abdominal distention, nausea, vomiting and edema in lower limbs for 1 month. Laboratory data sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 16 publications
0
6
0
4
Order By: Relevance
“…Notably, certain individuals may remain asymptomatic, often leading to misdiagnoses as sporadic hypokalemia or hypomagnesemia. [3] Nonetheless, Severe adverse events have also been reported in the literature, encompassing growth retardation, [2,4] chondrocalcinosis, [5] generalized seizures, [6,7] non-periodic paralysis, [2] rhabdomyolysis, [8] and even cardiac arrest. [9] The course of GS typically follows a mild trajectory, characterized by predominantly modest clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, certain individuals may remain asymptomatic, often leading to misdiagnoses as sporadic hypokalemia or hypomagnesemia. [3] Nonetheless, Severe adverse events have also been reported in the literature, encompassing growth retardation, [2,4] chondrocalcinosis, [5] generalized seizures, [6,7] non-periodic paralysis, [2] rhabdomyolysis, [8] and even cardiac arrest. [9] The course of GS typically follows a mild trajectory, characterized by predominantly modest clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Both glucocorticoids and immunosuppressive agents are effective in the treatment of KD and nephrotic syndrome, which may re ect a similarity in the immunopathogenesis of these diseases [12] . Glucocorticoids are known to regulate lymphopoiesis and T cell proliferation, suggesting that defects in T cell immune regulation play a role in the their pathogenesis [13] ; cytokines released by activated T cells may increase the permeability of the glomerular basement membrane, leading to proteinuria [14,15] . We compared clinical data of patients with vs. without renal impairment, and found that the former had lower albumin and total protein levels although there were no differences in their clinical manifestations, eosinophil ratio, creatinine, etc.…”
Section: Discussionmentioning
confidence: 99%
“…An optimal therapy for KD is not defined due to the rarity of the disease, misdiagnosis and loss of follow-up. It is generally believed that KD-associated renal lesion is a benign course, only a few patients have been reported to progress to end-stage renal disease requiring dialysis [ 3 , 17 ]. Glucocorticoid is the first choice for medical treatment of KD with nephropathy [ 11 ], but it is easy to recur after glucocorticoids withdrawal or dose reduction [ 3 , 9 ].…”
Section: Discussionmentioning
confidence: 99%